Assassinations, Elections and Democracy – Ancient Athenian-Style - Cartledge, Paul (Classica et Mediaevalia, 2026)
Assassination is never a pleasant theme to contemplate, but in some contexts historians are bound not just to contemplate it but also to factor it in as a crucial variable in trying to explain major political transformation. Such a context is offered by the history of Athens between c. 514 and 411 BCE. Within that span four transformational assassinations occurred, of Hipparchus, Ephialtes, Androcles and Phrynichus. They were variously motivated, but all had significant immediate or longterm impact on the Athenian narrative, in this case the narrative of the world's foundational democracy. The essay that follows seeks to pay due tribute to the memory of the great scholar – and friend – who did more than anyone to enrich and explain that narrative.